Summary of the lean startup - Ries, Eric, ....- (S.l. : Instaread, 2016)
The Lean Startup offers a set of tools and methodologies for entrepreneurs both in startups and established corporations to better achieve success. Since the vast majority of startups fail, understanding how to build a better company saves society's most precious commodities: ideas, time, and the skills of its people. The lean startup movement sets out to prevent future failures…
Keywords: Ondernemen